INTERAKSI SOSIAL WANITA PEKERJA BADUY - Nazia Maulia Amini; Budiaman Budiaman; Nova Scorviana H (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2018)
Baduy tribe woman worker social interaction (case study baduy women who work in out of Baduy region), Education of Social Sciences program, Faculty of Social Sciences, Universitas Negeri Jakarta, 2017.The purpose of this research to take information related with: (1) Baduy women’s motivation who work in out of Baduy region; (2) Ways of Baduy women worker interaction when being at non-Baduy’s tribe area. This research was acted for 3 months at around of Baduy region (Ciboleger, Ciminyak, and Cihandam). The methodology that was used in this research is qualitative approach by studying case methode. While for data collection technic using: observation technic, interview technic, documentation analysis, and field notes. For data analysis in this research used some technic such as: analyze, reducing, providing data, and deducing.The result of this research brings at conclusion that: (1) Baduy women worker motivation caused by internal and external factors. Internal factor consist of: Self in motivation and unsatify of marriage. While factors external consists of: less of farming land for Huma nor empty agricultural land for Huma activities, financial independence, and need for home belonging. (2) As a woman worker, Baduy women will always do interaction proces within their working area in order to able in doing their works. In their interaction process, they will be improved artlessly by looking and imitation during in interaction process. Looking and imitation when in interaction process is substance indicates that people have strong motivation will hard effort finding solutions of problems were being facing. However, difference of background culture still become obstacle for Baduy women worker to be able interact good. The obstacles will appear when in using language, adapting with new culture, and low self confidence from Baduy women worker.